Quality assessment of rice seed using different storage techniques (Journal of the Bangladesh Agricultural University, 2016)
Rice (cv. BRRI Dhan28) seed from two sources (Farmer and BADC) were collected and stored in 10 different types of indigenous storage containers viz., i) earthen jar (EJ), ii) coaltar coated EJ, iii) seed mixed with neem leaves (Azedirecta indica) in EJ, iv) seed mixed with Biskatali leaves (Polygonum hydropiper) in EJ, v) biscuit tin, vi) drum, vii) hessian bag (HB), viii) hessian bag with polythene cover, ix) dole and x) cowdung coated dole for four months in the laboratory of the department of Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh. The changes of some quality components of seed such as moisture content, germination, insect and pathogen attack, protein and starch contents were monitored at certain interval over 120 days of storage. Containers were characterized into three categories viz., easily permeable, permeable and almost impermeable. In case of almost impermeable containers like biscuit tin, drum and hessian bag with polythene cover, seed moisture increased significantly with the advancement of storage period but did not exceed desired level. Moisture percentage of the seeds of biscuit tin, drum and hessian bag with polythene cover was 12.78, 12.95 and 12.88 %, respectively. Germination percentage of seeds in all impermeable containers was above 80 %. Seed mortality was found to be positively correlated with moisture content and storage duration. Seed borne pathogens were associated along with the seed. Field fungi like Alternaria, Curvularia, Cladosporium though observed initially, but in the last pathological test Aspergillus sp., Penicillium sp. and Fusarium sp. were found predominantly. Insect attack was severe in easily permeable containers. Permeable containers containing the leaves of neem and biskatali restricted insect and fungal attack. Seed protein and starch content varied with storage period. Starch content of seed was 77 % at 60 days of storage and decreased to 75 % at 120 days of storage. Significant superiority of BADC seed over the farmers seed irrespective of all the parameters studied was noticed. The overall observation suggests that, biscuit tin and drum could be used for small scale storage and hessian bag with polythene cover for bulk storage of rice seed for a certain period.J. Bangladesh Agril. Univ. 12(2): 297-305, December 2014